Environmental study satisfaction: case of public universities in Klang Valley - student's hostel room / Nur Adilla Abd Rahaman, Arniatul Aiza Mustapha and Azizan Nor - Abd Rahaman, Nur Adilla; Mustapha, Arniatul Aiza (Research Management Institute (RMI), 2010)
The purpose of this study is to provide an insight into the importance of understanding the environmental study for students in Malaysia's public universities. As for the beginning of this study, it will starts by conducting it among students which do stays in the hostels in public universities in Klang Valley. The selected universities for this study are Universiti Malaya (UM), Universiti Kebangsaan Malaysia (UKM), Universiti Putra Malaysia (UPM), and Universiti Teknologi MARA (UiTM). These selected universities are recognized as public university by the Ministry of Higher Education. Therefore, these are the selected universities that convenience for this purpose of study. Throughout the findings, we identified that students from the four selected universities are moderately satisfied with their hostel room. Studies have also shown that there are differences in satisfaction between subsamples of respondent relating the four (4) environmental factors (ventilation, lighting, sound and ergonomics) with universities, courses and years of study. The studies showed that there is a need of comfort and conducive room for student to be able to study as well relaxing. Therefore, there are opportunities for interior designers to study more about the hostel design in order to achieve comfort and balance study environment. Further research can be done on the ability of study, where it can be focus on the hostel room planning.